Shaping of Natural Killer Cell Antitumor Activity by Ex Vivo Cultivation - Granzin, Markus; Wagner, Juliane; Köhl, Ulrike; Cerwenka, Adelheid; Huppert, Volker; Ullrich, Evelyn (Frontiers in Immunology, 2017)
Natural killer (NK) cells are a promising tool for the use in adoptive immunotherapy, since they efficiently recognize and kill tumor cells. In this context, ex vivo cultivation is an attractive option to increase NK cells in numbers and to improve their anti-tumor potential prior to clinical applications. Consequently, various strategies to generate NK cells for adoptive immunotherapy have been developed. Here, we give an overview of different NK cell cultivation approaches and their impact on shaping the NK cell anti-tumor activity. So far, the cytokines interleukin (IL)-2, IL-12, IL-15, IL-18 and IL-21 are used to culture and expand NK cells. The selection of the respective cytokine combination is an important factor that directly affects NK cell maturation, proliferation, survival, distribution of NK cell subpopulations, activation and function in terms of cytokine production and cytotoxic potential. Importantly, cytokines can up-regulate the expression of certain activating receptors on NK cells, thereby increasing their responsiveness against tumor cells that express the corresponding ligands. Apart from using cytokines, co-cultivation with autologous accessory non-NK cells or addition of growth-inactivated feeder cells are approaches for NK cell cultivation with pronounced effects on NK cell activation and expansion. Furthermore, ex vivo cultivation was reported to prime NK cells for the killing of tumor cells that were previously resistant to NK cell attack. In general, NK cells become frequently dysfunctional in cancer patients, for instance by down-regulation of NK cell activating receptors, disabling them in their anti-tumor response. In such scenario, ex vivo cultivation can be helpful to arm NK cells with enhanced anti-tumor properties to overcome immunosuppression. In this review we summarize the current knowledge on NK cell modulation by different ex vivo cultivation strategies, focused on increasing NK cytotoxicity for clinical application in malignant diseases. Moreover, we critically discuss the technical and regulatory aspects and challenges underlying NK cell based therapeutic approaches in the clinics.